Lettuce irrigation scheduling using atmometers and computers - McSay, Ann Emery, author; Moore, Frank D., III, advisor; Workman, Milton, committee member; Angleton, George, committee member; Danielson, Robert E., committee member (Colorado State University. Libraries, 1980)
Linear relationships between soil matric potential (SMP) and evaporative power of the air (EPA) were developed in order to schedule irrigation of lettuce in arid or semi-arid regions. The irrigation scheduling model is based on the assumption that SMP i.e. soil moisture "need" is a function of stage of growth, EPA, soil texture and root zone recharge. Root zone recharge may be due to an irrigation which brings the effective root zone to field capacity or a rainfall event which accomplishes the same purpose. Four linear equations similar to stage of growth coefficients are modified by soil coefficients which account for variation in hydraulic conductivities due to soil texture. Information required on a daily basis for daily output consists of milliliters of water lost from standardized Bellani plant atmometers and inches of rainfall from 8 inch diameter USWS rain gauges. The irrigation scheduling output is in 2 forms. One is graphic. Graphic analysis allows the user to visualize the progression of SMP (converted from ƩEPA) as a function of days from last recharge. The observer simply compares this plotted line to the SMP horizontal (constant) line, one for each of the 4 growth stages. An obvious reminder of tardiness occurs after the two lines intersect. This graphic form of output results from a program written in assembly language for a programmable calculator. The other form of output is digital. A FORTRAN program for a large scale computer was written. The program fits, by the least squares method; linear, quadratic and cubic regression equations to ƩEPA versus days from last recharge data. The program solves each of the 3 polynomials for days to next recharge and converts the end of the interval to a calendar date. The user then selects the most imminent of the 3 predicted dates with the aid of associated coefficients of determination. A tardiness reminder is also provided. The program is used in the interactive mode and will permit rapid daily update and query of 400 different plantings. A method was developed to protect the Bellani plate assemblies from freezing.
Covers not scanned.
Keywords: Lettuce -- Irrigation